FACTORS AFFECTING TREATMENT DURATION - A DILEMMA IN ORTHODONTICS - Faruqui, Saman; Fida, Mubassar; Shaikh, Attiya (Journal of Ayub Medical College Abbottabad, 2018)
Background: One of the first concerns of new orthodontic patients, apart from the outcome, is the duration of treatment. A better understanding of orthodontic treatment duration as well as factors affecting the treatment duration is useful for efficient patient counselling and improved clinical practice. Hence, the objectives of this study are to compare the treatment durations of subjects with Class I and Class II division 1 (II/1) malocclusions, and to identify the factors affecting the treatment duration of these malocclusions. Methods: This was a chart review conducted in the orthodontic department of the Aga Khan University Hospital, Karachi. The study sample comprised of 120 subjects and data were recorded from their treatment records. ANOVA and Bonferroni post-hoc were performed to determine the difference in treatment durations of Class I and Class II/1 malocclusions, whereas multiple linear regression was applied to identify the factors affecting the treatment duration. A level of significance (p‰¤0.05) was used for the statistical tests. Results: A statistically significant difference was found between the treatment durations of Class I and Class II/1 non-extraction (p=0.007), Class I non-extraction and Class II/1 extraction (p=0.001), and Class I and II/1 extraction (p=0.004) groups. The factors significantly increasing the treatment duration included missed appointments, breakages, and lower incisor proclination. Conclusion: Orthodontic treatment of Class II/1 malocclusion lasts longer than that of Class I malocclusion. Prolonged treatment time is associated with missed appointments, band/bracket debonds and increased lower incisor inclination. The variance in treatment time can be explained most significantly by number of missed appointments and breakages Keywords: Class-I malocclusion; Class-II/1 malocclusion; treatment duration; missed appointments; breakages